2017
DOI: 10.1038/s41598-017-02993-6
|View full text |Cite
|
Sign up to set email alerts
|

A Haptotaxis Assay for Neutrophils using Optical Patterning and a High-content Approach

Abstract: Neutrophil recruitment guided by chemotactic cues is a central event in host defense against infection and tissue injury. While the mechanisms underlying neutrophil chemotaxis have been extensively studied, these are just recently being addressed by using high-content approaches or surface-bound chemotactic gradients (haptotaxis) in vitro. Here, we report a haptotaxis assay, based on the classic under-agarose assay, which combines an optical patterning technique to generate surface-bound formyl peptide gradien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…In this sense, the PD-1/PD-L1 axis blockage is a promising therapeutic tool that is being successfully used in several types of malignant tumors, including kidney [67], breast [68], lung [69] and bladder [70] cancers, as well as malignant melanoma [71]. Chemotaxis can be associated to the so-called haptotaxis, which refers to the directional motility induced by a gradient of cell adhesion [34] and differs from chemotaxis in the nature of the chemoattractant molecule. So, the chemoattractant is soluble in chemotaxis and insoluble (linked to the extracellular matrix) in haptotaxis.…”
Section: External Stimuli Migration and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, the PD-1/PD-L1 axis blockage is a promising therapeutic tool that is being successfully used in several types of malignant tumors, including kidney [67], breast [68], lung [69] and bladder [70] cancers, as well as malignant melanoma [71]. Chemotaxis can be associated to the so-called haptotaxis, which refers to the directional motility induced by a gradient of cell adhesion [34] and differs from chemotaxis in the nature of the chemoattractant molecule. So, the chemoattractant is soluble in chemotaxis and insoluble (linked to the extracellular matrix) in haptotaxis.…”
Section: External Stimuli Migration and Cancermentioning
confidence: 99%
“…In fact, galvanotaxis and chemotaxis have been documented in unicellular eukaryotic organisms as far as more than one hundred years ago [ 33 ]. In addition, other dynamic forces of cell guidance such as haptotaxis [ 34 , 35 ], barotaxis [ 36 , 37 ], durotaxis [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], topotaxis [ 47 , 48 ] and plithotaxis [ 49 , 50 , 51 ] have been described latterly as additional conditioning factors of cell migration.…”
Section: External Stimuli Migration and Cancermentioning
confidence: 99%
“…Rink et al, experimentally showed neutrophil CXCR1/CXCR2‐mediated haptotaxis using custom agarose stamps to micropattern IL‐8 binding sites on glass substrates . Using a laser‐assisted protein adsorption method, to reproduce substrate bound formyl‐peptide concentration gradients, formyl peptide receptor (FPR)‐mediated haptotaxis was demonstrated . The FPR‐activated pathway dominates the CXCR1/CXCR2 pathway; formyl peptides are actively released by invading pathogens or passively released from dead/dying host cells, and homing and phagocytosis is immunologically more crucial.…”
Section: Reverse Engineering Of the Immune Microenvironmentmentioning
confidence: 99%
“…Streptavidin was then bound to immobilize B4F followed by biotin‐conjugated chemokine binding to streptavidin to generate immobilized chemokine gradients. This technology have been used in quantitatively investigating DC haptotaxis following the immobilized CCL21 gradients and compete chemotaxis following soluble CCL19 gradients, and comparative study of neutrophil haptotaxis and chemotaxis guided by formyl‐peptide gradients . Since the combination of chemo‐ and haptotactic guidance cues plays a fundamental role in both physiological processes such as protective immunity and tissue regeneration and pathogenesis of diseases such as cancer metastasis and autoimmunity, assessing the migratory response of cells guided by well‐controlled coexisting chemotactic and haptotactic cues in vitro has the potential to significantly contribute to a better understanding of migration‐related physiological and pathological processes.…”
Section: Immune Cell Migration On a Chipmentioning
confidence: 99%